2015
DOI: 10.1002/advs.201500002
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐Up Synthesis of Fragrant Nitrogen‐Doped Carbon Dots from Bee Pollens for Bioimaging and Catalysis

Abstract: Fragrant nitrogen‐doped carbon dots of gram scale can be prepared from commercial bee pollens by a hydrothermal process. These carbon dots of 1–2 nm in size show promising applications in cellular imaging and catalysis/photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
93
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 58 publications
2
93
1
3
Order By: Relevance
“…However, it is still challenging to prepare carbon dots from biomass in a quite reproducible manner. Very recently, we proposed to prepare photoluminescent carbon dots from one-pot hydrothermal treatment of bee pollen in a highly reproducible way [8]. Apart from synthesis, the carbon dots are used for sensing of metal ions [9], optical bioimaging [10], photocatalysis [11], and photo-induced electron transfer (PET) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still challenging to prepare carbon dots from biomass in a quite reproducible manner. Very recently, we proposed to prepare photoluminescent carbon dots from one-pot hydrothermal treatment of bee pollen in a highly reproducible way [8]. Apart from synthesis, the carbon dots are used for sensing of metal ions [9], optical bioimaging [10], photocatalysis [11], and photo-induced electron transfer (PET) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that the fluorescence of the carbon dots barely changed in the presence of a variety of metal ions and anions [8]. Utilizing Au or Ag nanoparticle (NP) as the light absorber and carbon dots as the fluorophore, we then fabricated a turn-on fluorescent sensor for cyanide on the basis of inner filter effect (IFE) of metal nanoparticles [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most probably, more carboxyl groups conjugate more amino groups on NCDs' surface, which leads to higher FLQY. [33][34][35][36] The UV-Vis absorption spectra are shown in Fig. 5(b).…”
mentioning
confidence: 99%
“…Therefore, N-GQDs were capped on electrode surface with chitosan in this study. Using N-GQDs as luminescence label and catalyzer Zhang et al, 2014Zhang et al, , 2015aZhang et al, , 2015bShen et al, 2012;Valizadeh et al, 2015), an ECL enhancement sensing system was designed (Scheme 1). In the sensing system, N-GQDs were capped on electrode surface with chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, luminescent methods have been combined with electrochemical techniques to expand GQDsbased sensing applications (Liu et al, 2014;Wu et al, 2015). And researchers have established kinds of N-GQDs-based ECL sensors which were successfully used to detect small molecules, organic compounds, protein, and so on (Zhang et al, 2015a(Zhang et al, , 2015bZhou et al, 2015;Du et al, 2015;Wang et al, 2015aWang et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%